Elements of the physical environment attractive to kindergarten child from the point of view of kindergarten teachers and principals; Khamis Mushait Governorate: Descriptive study - Kadi, Laila Abdullah Ahmed; Al-Hazmi, Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2021)
The aim of this study was to know the physical elements that attract the child in the kindergarten. Using the descriptive method, the researcher established a questionnaire to know the point of view of female managers and teachers at kindergartens in Khamis Mushait governorate. The questionnaire included 54 items which underwent scientific revision by experts in the same field to confirm their validity and reliability. The study sample was randomly selected from the managers and teachers and contained 144 samples.The main results of the study denoted that the average response on the first section (the building of the kindergarten) was 3.06, while the response on the second section (resources) was lower. As regard to the third section which involved the safety and security in the building.In addition, there were no statistically significant differences in the responses regarding the variables: work nature, experience, or specialty in all the sections of the questionnaire.The main recommendations for this study were to take into consideration the international standards for the kindergarten buildings and to provide the main resources and equipment needed in the building and teaching classes and as well as safety and security needs.
Keywords: Physical environment; Attractive environment; Kindergarten child; Kindergarten